Perlindungan Hukum terhadap Debitur Kredit Macet Akibat Praktek Cessie dalam Perjanjian Perbankan - Juliman; Kadek Wiwik Indrayanti (Postgraduate University of Merdeka Malang, 2025)
Debtors who default often make creditors choose a quick mechanism to recover their receivables, one of which is through cession or the transfer of receivables to a third party. Although the practice of cession is legal and recognized in the Indonesian legal system, until now there is no specific regulation that specifically regulates the procedure, thus opening the opportunity for actions that are detrimental to debtors, especially those who have relatively small remaining debts but are still the object of transfer without adequate notification. This study uses a normative method with a descriptive analytical approach to examine the regulation of cession and legal protection for debtors. Legally, cession is regulated in the Civil Code Book III on Contracts as well as several special regulations such as the Mortgage Law, the Fiduciary Law, and Bank Indonesia provisions. In principle, cession can be carried out as long as it is agreed by the parties through a new agreement. However, if the transfer of receivables is carried out without notification to the debtor, the agreement is potentially invalid because the object of the receivable is still attached to the debtor. Thus, the transfer of receivables that is not informed to the debtor can be cancelled or even void by law, thus providing legal protection for the debtor from the implementation of a detrimental assignment.